The Transition Towards Slow Fashion: A Bibliometric Analysis of Sustainable Consumer Behavior and Future Research Opportunities - Naila, Muthia; Noer, Lissa Rosdiana (Dinasti International Journal of Economics, Finance & Accounting, 2025)
The growing global concern for sustainability in the fashion industry underscores the need for a comprehensive scientific mapping of trends in slow fashion and sustainable consumer behavior. This study employs a quantitative-descriptive bibliometric approach, analyzing 137 scholarly documents published between 2014 and the first quarter of 2025. The analysis utilizes Biblioshiny to generate descriptive statistics and thematic maps, while VOSviewer is used to visualize keyword co-occurrence networks and author collaborations. The results reveal a significant annual growth in publications, dominated by themes such as sustainability, consumer behavior, and the fashion industry. The United States emerges as the most prolific contributor, with the Journal of Fashion Marketing and Management being the primary source of publications. Keyword mapping highlights major thematic clusters related to ethical consumption, circular economy, and purchase intention. The thematic map positions slow fashion as an emerging yet underdeveloped theme with considerable academic potential. This study emphasizes the importance of adopting a more holistic perspective by integrating qualitative methods, expanding geographic contexts to include the Global South, and exploring the role of digital technologies and social dynamics in driving more equitable and sustainable fashion consumption behavior.